PENYULUHAN PEMANFAATAN PANGAN LOKAL SEBAGAI UPAYA PENCEGAHAN STUNTING - Masitah, Ravi; Fanany, Irzal; Nurmala Dewi, Siti; Dessritina, Pesona (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Stunting is a type of malnutrition that has an impact on the growth and development of children that is not optimal. Fulfilling nutritional adequacy through local food is the right effort to prevent the occurrence of stunting. The use of local food that has high nutritional value at affordable prices can be a solution to solving nutritional problems. Fish is a local food ingredient fulfilling the nutritional adequacy of children through the use of local food, namely fish can be an alternative to solving stunting problems. The activities carried out were in the form of counseling on the use of local food to prevent stunting using flyer media. The service activity was carried out in Sungai Pinang Village, Banyuasin Regency in December 2023. The target of the activity was pregnant women, baby mothers and mothers of toddlers as many as 30 people. The results of the activity showed that the average value of maternal nutrition knowledge before being given counseling was 37.00 and increased to 81.00 after being given counseling. Counseling is expected to help mothers in increasing knowledge that will affect maternal nutritional attitudes and behaviors in efforts to prevent stunting.